2012
DOI: 10.1039/c2lc20705b
|View full text |Cite
|
Sign up to set email alerts
|

Nebulisation on a disposable array structured with phononic lattices

Abstract: We demonstrate the use of a phononic crystal to enable the nebulisation of liquid droplets from low-cost disposable arrays, using surface acoustic waves (SAW). The SAWs were generated using interdigitated transducers (IDT) on a piezoelectric surface (LiNbO(3)) and the acoustic waves were coupled into a disposable phononic crystal structure, referred to as a superstrate. Using its excellent reflecting properties, the phononic structures confined the acoustic field within the superstrate, resulting in the concen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
35
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 32 publications
(46 reference statements)
0
35
0
Order By: Relevance
“…1,2,7-9 Among these streaming phenomena, surface acoustic wave nebulization (SAWN) has been studied extensively due to its wide potential applications in targeted drug delivery, patterning of nanoparticles, cell or protein generation, inhalation therapy, mass spectrometric analysis, deposition of biochemical films, etc. [9][10][11][12][13][14][15][16] Recently, there has been an increasing interest in SAW based microfluidic devices using high performance piezoelectric thin film materials, such as ZnO. [17][18][19][20][21] These ZnO films, typically a few micron thick, deposited on silicon, glass, or polymer, have advantages compared with using bulk materials such as LiNbO 3 or quartz.…”
mentioning
confidence: 99%
“…1,2,7-9 Among these streaming phenomena, surface acoustic wave nebulization (SAWN) has been studied extensively due to its wide potential applications in targeted drug delivery, patterning of nanoparticles, cell or protein generation, inhalation therapy, mass spectrometric analysis, deposition of biochemical films, etc. [9][10][11][12][13][14][15][16] Recently, there has been an increasing interest in SAW based microfluidic devices using high performance piezoelectric thin film materials, such as ZnO. [17][18][19][20][21] These ZnO films, typically a few micron thick, deposited on silicon, glass, or polymer, have advantages compared with using bulk materials such as LiNbO 3 or quartz.…”
mentioning
confidence: 99%
“…By their natural frequency selective characteristics and guiding capabilities they can play a major role in developing lab on chip applications. Reboud et al have demonstrated the capability of phononic crystal structures in handling liquids [16][17][18]. Various functions such as microcentrifugation of particles and blood cells and selective nebulization of liquid micro-droplets have been demonstrated to be very effective using phononic crystal structures.…”
Section: Phononic Crystals For Liquid Control and Handlingmentioning
confidence: 97%
“…1 These waves can couple into thin plates, placed on the piezoelectric material, where they propagate as Lamb waves. 2 When a liquid is placed in the propagation path of such waves, on a thin plate, the ultrasonic wave refracts into the fluid with a transfer of mechanical energy and radiative pressure that leads to fluid streaming, Fig. 1.…”
Section: Introductionmentioning
confidence: 99%